SOFTWARE FOR SCHEDULING AND MANAGING MEDICAL APPOINTMENTS OVER THE INTERNET (CIPEEX, 2024)
THE PROJECT IS A SOFTWARE FOR SCHEDULING AND MANAGING MEDICAL APPOINTMENTS OVER THE INTERNET. IT AIMS TO SIMPLIFY THE BOOKING OF APPOINTMENTS IN THE PRIVATE NETWORK, WITH PLANS TO EXPAND TO THE PUBLIC NETWORK. THE SOFTWARE IS ACCESSED BY DOCTORS, SECRETARIES, AND PATIENTS, ALLOWING THEM TO SCHEDULE APPOINTMENTS AND MANAGE MEDICAL SCHEDULES. THE MAIN OBJECTIVE IS TO FACILITATE THE SCHEDULING OF MEDICAL APPOINTMENTS AND OPTIMIZE THE AVAILABLE SCHEDULES. THE SOFTWARE WILL ALSO PROVIDE REPORTS TO ASSIST IN APPOINTMENT OPTIMIZATION. IT USES JAVASCRIPT/TYPESCRIPT WITH REACT FOR THE WEB VERSION AND REACT NATIVE FOR MOBILE, ALONG WITH A BACKEND IN NEST.JS. THE PLATFORM OFFERS A REAL-TIME SHARED SCHEDULE AND BUSINESS RULES FOR APPOINTMENT CONTROL. THE SOFTWARE PROVIDES THE ABILITY TO VIEW THE SCHEDULES OF VARIOUS DOCTORS AND THEIR AVAILABLE TIME SLOTS, ALLOWING PATIENTS TO SCHEDULE APPOINTMENTS QUICKLY AND CONVENIENTLY. THIS ELIMINATES THE NEED TO CALL MEDICAL OFFICES TO MAKE APPOINTMENTS. THE PROJECT USES AGILE METHODOLOGIES, SUCH AS SCRUM, AND A VISUAL TASK MANAGEMENT SYSTEM, SUCH AS TRELLO, TO ORGANIZE DEVELOPMENT. THE CREATION OF A PROCESS FLOW AND THE DEFINITION OF INITIAL TASKS ESTABLISH A SOLID FOUNDATION FOR FUTURE DEVELOPMENT. THE PROJECT HAS THE POTENTIAL TO POSITIVELY IMPACT THE HEALTHCARE SECTOR, MAKING THE MANAGEMENT OF MEDICAL APPOINTMENTS MORE EFFICIENT AND ACCESSIBLE. THE NEXT STEPS WILL INVOLVE CREATING PROTOTYPES, CODING, AND IMPLEMENTING THE MENTIONED TECHNOLOGIES.
Keywords: Appointments; Medical Appointments; Appointment Scheduling; Shared Agenda; Health